Shedding light on AWARE : branding AWARE through the viral marketing of an animated promo. - See, Magdalene Huiling. (2008)
Shedding Light on AWARE is a promotional campaign that aims to increase the visibility of the Association of Women's Action and Research (AWARE) in Singapore, with the ultimate goal of increasing supports and members for the voluntary welfare organization.